A decade after #YoSoy132: approaches, scope of the movement and the dynamics that promoted it from Twitter - Nemecio, Andrómeda Martínez (2023)
A decade after the #YoSoy132, a student movement that gained notoriety in the global traditional and digital media agenda, is investigated the role of Twitter in the emergence of the event that meant the first relevant call to collective action in the Internet and social media era in Mexico. Based on a Bauman typology of leaders of authority, it was found among the 50 most retweeted messages that promoted the hashtag #YoSoy132, in May 2012, the presence of dynamics observed since the days of the mass media, such as agenda setting and the two-step flow theory. This points to the permanence of traditional media opinion leaders as gatekeepers who filter the information they consider relevant from the digital environment, but where there are also leaders of authority: social actors who make the collective demands visible within the current media environment.